1997
DOI: 10.1111/j.1442-9071.1997.tb01742.x
|View full text |Cite
|
Sign up to set email alerts
|

Cataract surgery reduces subjective visual disability

Abstract: Nuclear and PSC cataracts cause more visual disability than cortical cataracts. Visual disability is significantly reduced by cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…7,10,[36][37][38][39][40][41] However, the postoperative visual acuity in the betterseeing eye of patients who had surgery in both eyes was significantly better (by almost 2 lines) than the visual acuity in the operated eye of first-eye surgery patients. Similarly, the postoperative visual acuity in the operated eye of the second-eye surgery patients was significantly better (by 1.3 lines) than that in first-eye surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“…7,10,[36][37][38][39][40][41] However, the postoperative visual acuity in the betterseeing eye of patients who had surgery in both eyes was significantly better (by almost 2 lines) than the visual acuity in the operated eye of first-eye surgery patients. Similarly, the postoperative visual acuity in the operated eye of the second-eye surgery patients was significantly better (by 1.3 lines) than that in first-eye surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pesudovs and Coster [2] found that, in an analysis for relationship between LOCS III of cataract severity and visual disability score measure, nuclear and posterior subcapsular (PSC) cataract caused more visual disabilities than cortical cataracts. They concluded that this finding might reflect a problem with the LOCS III scoring system because clinical experience suggested that cortical cataracts could cause disability.…”
mentioning
confidence: 99%
“…However, all cataract patients were drawn from the cataract-surgery waiting list, and the key indicator for cataract surgery is, precisely, visual disability attributed to cataract. [32][33][34] Therefore, this population, by definition, does have visual disability, a fact that was also previously demonstrated. 35 A lack of unidimensionality was a second limitation of the AVL scale in the present study.…”
Section: Discussionmentioning
confidence: 59%